Gambaran kualitas hidup remaja yang overweight di SMA Unklab Airmadidi Kabupaten Minahasa Utara - Pasaribu, Haholongan Evlyn Rezky; Monintja, Tyrsa Christine Natalia; Siagian, Iyone Esra Tiurma (Jurnal Kedokteran Komunitas dan Tropik, 2023)
Background: Adolescence represents a transitional phase between childhood and adulthood, which spans from ages 10 to 19. One of the health issues faced by adolescents is overweight. Overweight continues to be a global concern, enduring as a persistent health challenge for low-income countries, including Indonesia. Research conducted in Manado City shows that approximately 14.9% of adolescents are overweight. The impact of being overweight can significantly affect an individual's quality of life. Studies have demonstrated that overweight adolescents tend to have a lower quality of life compared to their counterparts with normal body weight. This phenomenon arises from weight-based victimization experienced by overweight adolescents.Aim: To ascertain the quality of life among overweight adolescents at SMA Unklab Airmadidi, North Minahasa Regency.Methods: This research employs a descriptive research design with a cross-sectional approach, involving 364 respondents, including 63 overweight students.Results: The findings of this research show that overweight adolescents have moderate quality of life in the domains of physical health, psychology, and social aspects. However, in the environmental domain, the quality of life is good.Conclusion: The majority of overweight adolescents have moderate quality of life in the domains of physical health, psychology, and social well-being. Conversely, they exhibit good quality of life in the environmental domain.Keywords: adolescents; overweight; quality of life